Salesforce Incentives, Market Information, and Production/Inventory Planning - Chen, Fangruo (Management Science, 2005)
Salespeople are the eyes and ears of the firms they serve. They possess market knowledge that is critical for a wide range of decisions. A key question is how a firm can provide incentives to its salesforce so that it is in their interest to truthfully disclose their information about the market and to work hard. Many people have considered this question and provided solutions. Perhaps the most well-known solution is due to Gonik (1978), who proposed and implemented a clever scheme designed to elicit market information and encourage hard work. The purpose of this paper is to study Gonik's scheme and compare it with a menu of linear contracts—a solution often used in the agency literature—in a model where the market information possessed by the salesforce is important for the firm's production and inventory-planning decisions.